2021
DOI: 10.1002/smtd.202001042
|View full text |Cite
|
Sign up to set email alerts
|

Near‐Infrared‐Responsive Photocatalysts

Abstract: Broadening the absorption of light to the near‐infrared (NIR) region is important in photocatalysis to achieve efficient solar‐to‐fuel conversion. NIR‐responsive photocatalysts that can utilize diffusive solar energy are attractive for alleviating the energy crisis and environmental pollution. Over the past few years, considerable progress on the component and structural design of NIR‐responsive photocatalysts have been reported. This study aims to systematically summarize recent progress toward the material d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
56
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 122 publications
(56 citation statements)
references
References 181 publications
0
56
0
Order By: Relevance
“…[62] Some metal NPs such as Au, Ag, and Cu can harvest visible light to generate e − 's via surface plasmon resonance (SPR) excitation, [63] expanding the absorption range into the visible-light region. [64,65] As early as 2010, Teranishi et al deposited Au NPs on anatase TiO 2 and observed enhanced H 2 O 2 production, achieving a yield over 10 mmol L −1 . [66] The oxidation and reduction sites were TiO 2 and Au NPs, respectively.…”
Section: Deposition Of Metal Nanoparticlesmentioning
confidence: 99%
“…[62] Some metal NPs such as Au, Ag, and Cu can harvest visible light to generate e − 's via surface plasmon resonance (SPR) excitation, [63] expanding the absorption range into the visible-light region. [64,65] As early as 2010, Teranishi et al deposited Au NPs on anatase TiO 2 and observed enhanced H 2 O 2 production, achieving a yield over 10 mmol L −1 . [66] The oxidation and reduction sites were TiO 2 and Au NPs, respectively.…”
Section: Deposition Of Metal Nanoparticlesmentioning
confidence: 99%
“…In 2 S 3 has a narrow band gap of 2.0-2.3 eV, which has been extensively studied in photocatalysis and recognised as a promising candidate for heterojunction formation with TiO 2 [39][40][41]. Recently, a new concept of step-scheme (S-scheme) heterojunction has been proposed [42].…”
Section: Introductionmentioning
confidence: 99%
“…UV and visible light can be directly utilized to induce the formation of photogenerated carriers via the modification of photocatalysts, including narrowing the band gap, decorating with photosensitizers, building heterojunctions, and so on. Nevertheless, the energy of infrared light is not enough to directly excite the electron transition in photocatalysts . Therefore, the strategies of upconversion and photothermal conversion were developed to convert near-infrared light into high-energy light or heat, respectively, which can increase photogenerated carriers or change their behavior .…”
Section: Introductionmentioning
confidence: 99%